Effective Communication in Midwifery Practice Strengthening Patient Trust and Maternal Health Outcomes - Ainun Ganisia; Muhammad Khofidul A'zdom (Professorline, 2025)
Effective communication forms the foundation of safe and high-quality midwifery care. Beyond the transmission of medical information, communication in midwifery involves empathy, respect, and therapeutic interaction that build trust and improve maternal experiences. In Indonesia, communication competence among midwives plays a crucial role in achieving national maternal health goals and reducing preventable complications. This paper explores the conceptual framework and practical relevance of effective communication in midwifery practice, emphasizing its role in strengthening patient trust, improving service satisfaction, and enhancing maternal health outcomes. Using a descriptive qualitative and literature-based approach, this study synthesizes theoretical and empirical evidence from midwifery, communication, and behavioral health disciplines. Sources from 2018–2025, including textbooks, journal articles, and WHO and ICM guidelines, were analyzed through narrative synthesis focusing on three key dimensions: interpersonal, informational, and therapeutic communication. The analysis revealed that effective midwifery communication characterized by active listening, empathy, and clarity significantly increases maternal trust, adherence to care, and satisfaction with services. Communication also reduces anxiety, facilitates early complication detection, and strengthens interprofessional collaboration within maternity teams. Barriers such as workload, cultural diversity, and time constraints highlight the need for continuous professional development and institutional support. Effective communication is a clinical skill that integrates emotional intelligence with technical expertise. By embedding communication training into midwifery education and policy standards, healthcare systems can foster trustful, patient-centered relationships that contribute to improved maternal and neonatal health outcomes.